Introduction (Deep Foundations Institute, 2004)
"The development of non-destructive testing (NDT) methods for deep foundations occurred in several parts of the world, gradually coming together into the present state of the art. The compilation of this brief NDT history is the best effort of several knowledgeable members of the Deep Foundations Institute (DFI) Drilled Shaft Committee, coupled with the recollections of several historically important contributors to the science. It is not intended to be exhaustive, but rather concentrates on the origins of the methods in common use and on which this manual focuses.Modern NDT methods, and the spread of knowledge about them, have expanded through application to real foundations projects by the original researchers, sometimes inspired by their own curiosity, sometimes to respond to the cost and time limitations imposed by static testing, and sometimes to address the questions raised on research projects funded by large government agencies such as the Federal Highway Administration (FHWA) in the USA, and various European transportation agencies. Initial attempts were primitive by today’s standards, and equipment limitations often restricted successful application to relatively simple cases. As electronics improved and confidence in them increased, the early researchers began commercial promotion of their methods, published their findings in professional journals, and shared experiences at conferences held by such groups as the DFI, the International Association of Foundation Drilling (ADSC), the International Conferences on the Application of Stress-Wave Theory to Piles and other venues such as ASCE and Transportation Research Board (TRB) conferences.NDT methods were developed to fill a need to assess the quality assurance of deep foundation elements. New pile types and higher design loads prompted engineers to verify the safety of their foundations via additional testing during construction. Static load testing was the traditional method to assess performance, and this method has been used for centuries and perhaps even millennia.Relatively recent alternatives to static load testing for determining the capacity of drilled shafts include the bottom load test method. This method uses a jack embedded in the lower portion of the pile (bottom load test) and was first reported to be used from Canada in the early 1970’s (Gibson& Devenny 1973). The concept immediately caught on in Israel, where it was used as a quality control measure for small-diameter piles drilled in rock (then a new technology). The method was later patented in the US by Jorj Osterberg, and offered as a commercially available service in thelate 1980s (Osterberg, 1989)"